The Effect of Entrepreneurship Education, Personality, and the Role of Parents Through Self Efficacy on Interest in Entrepreneurship - Pertiwi, Ulfa Reza; Khafid, Muhammad (Economic Education Analysis Journal, 2021)
This study aimed to determine the effect of entrepreneurship education, personality, and the role of parents through self efficacy towards the interest in entrepreneurship. The population in this study were all students of class XI of SMK PGRI Blora 2017/2018 academic year totaling 127 students. This study used a saturated sample technique using the population as a study sample. Methods of collecting data used a questionnaire. The data analysis method used descriptive statistical analysis and path analysis. The results showed that (1) Entrepreneurship education, personality, self-efficacy had a positive and significant effect on the interest in entrepreneurship, but not with the role of parents who did not positively and significantly affect the interest in entrepreneurship (2) Entrepreneurship education, personality, and parental roles had a positive and significant effect on self efficacy (3) Self efficacy positively and significantly mediated entrepreneurship education, personality, and the role of parents in the interest in entrepreneurship.